ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI INFORMASI PELAPORAN KEUANGAN PEMERINTAH DAERAH PADA BPK-AD KANTOR WALIKOTA MANADO - Thebora, Patras; Morasa, Jenny; Rondonuwu, Sintje (Universitas Sam Ratulangi, 2017)
The objective of this research is to examine the factors that influence information value of local government financial reporting. Information value refers to reliability and timeliness. The factors that influence reliability and timeliness are human resource quality, information technology utilization,internal control system, and local financial monitoring.Local government financial management must be done according to the good governance, that are transparent and accountable, that allow users of financial statement to acces about theresult that local government accomplish. The objective of this research is to investigate the impact of human resources quality, utilization of information technology, local government financial controlling, and internal control system toward value of financial report information, which is timeliness. The research is talking place in BPK-AD of Mayor’s Office, Manado. The research method used is quantitative, and the sample is all the population of the officer that works for the research object. The hypothesis test conclude that human resources quality, and utilization of information technology do not have significant impact, while local government financial control and internal control system do have significant effect towards timeliness of financial reporting in BPK-AD of Mayor’s Office, Manado.Keyword : Information value, Local Government Financial Report, Human resource quality, utilization of information technologies, local government financial control, and internal control system